Nix the BRICs—At Least for Higher Education Scholarship - Altbach, Philip G.; Malee Bassett, Roberta (Taylor and Francis, 2014)
Although the “BRIC” moniker for the group of emerging economic powers—Brazil, Russia, India, and China—has become ubiquitous among financial analysts, it was actually coined by former Goldman Sachs economist Jim O’Neill as much for its clear imagery as for any actual commonalities amongst the countries (O’Neill, 2001). The bloc is even less relevant in understanding the complex higher education environments in these or other emerging economic powers such as Mexico, Indonesia, Nigeria, and Turkey (for which O’Neill has coined another clever acronym: the MINTs).